The time-factor in orthodontics: What influences the duration of treatments in National Health Service practices? - Turbill EA, Richmond S, Wright JL (Blackwell Synergy, 2001)
This study aimed to elucidate factors associated with duration of orthodontic treatment. Methods: Retrospective analysis of a systematic 2% sample of cases completed in National Health Service practices in England and Wales. Records were collected during 1991. Characteristics of practitioners, patients, malocclusions, treatment variables and outcomes were evaluated. Data were submitted to multivariate analysis, with Log10 Time in Treatment as the dependent variable.